On the Time and Place of the Printing of Francysk Skaryna’s Little Traveler’s Book - Lemeškin, Ilja (Knygotyra, 2019)
As we continue to solve the issues of book science of the 16th century, we have to be very guarded in questions of terminology. This is of particular importance when we talk about the Little Traveler’s Book, which begins the history of typography in the Grand Duchy of Lithuania. There is a widespread belief that the abovementioned book was printed in Vilnius approximately in 1522. It would be more correct to say that the Little Traveler’s Book was completed in Vilnius. One of its parts – a set of eight Akathists and eight canons – could have been printed earlier in Prague. This hypothesis can be supported with several arguments. In contrast with the Acts and Epistles of the Apostles (the Apostle, 1525), the Little Traveler’s Book is not dated anywhere and in terms of content, it is a heterogeneous (composite) publication. Considering the content of the Little Traveler’s Book, the elements that particularly stand out are the Akathists and canons that contain unique wood engravings, endpieces, vignettes, borders, and initials. Two wood engravings were made by one “Master of the New Testament,” whose works were published in the Prague Book of Psalms (1517). The autonomy of an Akathist as a particular publication is accented by the publisher’s acrostic colophon, written in the last Akathist via initials. The Akathists housed in Wroclaw (Wroclaw University Library, No. 305071) can represent the Prague period of typography. E. Nemirovkij’s “evidence” regarding the Vilnius origin of the Akathist is incorrect.